Land allocation in subsistence economies and intra-familial time-use decisions - Nadege Miclanche Azebaze; Thomas Falk; Evelyn Korn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Classical household theory predicts that adolescents facing a developed labour market should invest in formal education. In contrast, it is obvious that adolescents in subsistence economies should choose learning-by-doing approaches to working on the family farm. However, it is unclear what determines optimal education choices among societies in transition from subsistence to labour-market integration. While education is generally the basic condition to enter the labour market, access to land represents an important asset in subsistence farming. This paper argues that intra-household time use and education - that is, time spent learning outside the family farm - is influenced by the way land is transferred from one generation to the next. We use a dichotomous approach assuming that land is either transferred by bequest or by a formal land board. These two methods represent the extremes of a scale that considers personal relations and reliance on certified abilities as the basis for land allocation. This paper provides a theoretical analysis of how anticipated bequests and asset transfers from other sources influence trade-offs between work on the family farm and other time-use options. We discuss the effects using a case study from the Okavango.
Keywords: D13; D91; Q12; Q15; Q21; Q24; 330; Land allocation; inheritance rules; subsistence; intra-household decision making; intergenerational property transfer; education